Patterns of criminality and alcohol abuse: results of the Tuebingen Criminal Behaviour Development Study - Kerner, Hans-Jürgen; Weitekamp, Elmar G. M.; Stelly, Wolfgang; Thomas, Jürgen (Criminal behaviour and mental health, 1997)
This paper examines, first, the official German criminal police statistics in order to elucidate the role of alcohol with regard to the commitment of crimes and, second, the relationship of alcohol abuse and chronic offenders in a life course perspective. The results, based on the Tuebingen Criminal Behaviour Development Study TCBDS, show that the more a person is involved in crime the more he is drinking. But neither early experiences of socialisation nor imprisonment experiences are sufficient causal conditions for a heavy alcohol consumption in later life. The analyses indicate that alcohol abuse is an expression of the typical behavioural patterns and daily routine of criminals. Delinquency, alcohol consumption and a deviant lifestyle seem to interact and to enhance each other in the sense of an increasing spiral which leads to a decrease in opportunities for developing and maintaining a normal, socially integrated biography. Nevertheless heavy drinking in the past does not prohibit processes of desistance but desistance from crime goes hand in hand with desistance from heavy drinking. Copyright Ř 1997 Whurr Publishers Ltd